Are Strategies for New Product Development effect on Venture Sustainability in Ethiopia? - Wakjira, Gada Gizachew; Kant, Shashi (MultiTech Publisher, 2023)
The purpose of the study was to determine how New Product Development Strategies significantly impact Managerial Venture Sustainability. The case of Bule Hora University, Ethiopia, and the research philosophy of research paradigms that must be designed in quantitative and deductive research approaches, and researchers have used an exploratory factor analysis (EFA), research design, and the researchers are using the stratified sampling technique, and simple random sampling techniques, as well as a method of data collection from academic staff, administrative staff, and university customers, and the researchers. The data analysis was describe the information that can be analysed from the exploratory factor analysis, based on the correlation matrix, KMO, average variance extracted, factor loading, rotation matrix analysis, scatter plot, and construct the internal consistence of Convergent validity. And it was founded that Strategies for New Product Development effect on Venture Sustainability in Ethiopia. Therefore policy makers should focus more on Strategies for New Product Development for Venture Sustainability